Democracy and state creation in international law - Vidmar, Jure (2009)
At the end of the Cold War some scholars argued that democracy is the only legitimate political system and that this needs to be acknowledged even by international law. This thesis rejects such arguments and takes the position that attributes of statehood are not dependent on type of government. As far as existing states are concerned, democracy is not an ongoing requirement for statehood.